Kecerdasan Emosional Nabi Musa AS: Potret Pemimpin Ideal Perspektif Al-Quran: Potret Pemimpin Ideal Perspektif Al-Quran - Mushodiq, Muhammad Agus (Tapis: Jurnal Penelitian Ilmiah, 2018)
This study aims to examine the emotional intelligence of Prophet Musa as the leader of the Children of Israel in Surat al-Qasas. The stories displayed by the Quran are displayed in scriptable language, a language that is difficult to decipher. Based on this fact, the understanding of the story of Prophet Moses in the Qur'an will not be holistic without using the theory of interpretation, one of which is semiotics. To describe the emotional intelligence of Moses Prophet using the theory of semiotics Charles Sanders Peirce synergized with the theory of emotional intelligence Daniel Goleman. Inside Peirce semiotics marks are built on a triadic system. Three triadic points are representamen, object, and interpretan. In the presentation of research results, researchers used qualitative research methods. Description of research data is described with a holistic and radical narrative based on the theory used. The results of this study are (1) Prophet Moses is able to motivate his self and has high optimism, (2) able to overcome the aggressiveness of self, (3) able to overcome anxiety, (4) able to empathize, (5) wise, and (6) able assessing potential and self-awareness.